Comparing Angiotensin Gene polymorphisms According to Mechanical Ability for Weightlifter Selection - Sarmed Saad Hameed; Ghasan Adeeb Abd Al Hassan (College of Physical Education and Sport Sciences, 2020)
The research aimed at identifying polymorphisms of Angiotensin Gene for selecting young weightlifters and comparing these different forms with the mechanical ability for selecting youth weightlifters. The researchers used the descriptive method on (21) weightlifters whose average weight was (78.14 ±15.61) Km, height (1.73 ±0.08) m, and age (17.80 ±2.98) years. The results showed significant differences in favor of the experimental group that has the gene (D) in the mechanical ability variables of the snatch. In addition to that, there were no significant differences among the three groups who hold the genes (I, ID, D) respectively in mechanical ability variables during the clean and jerk. Finally, the researchers recommended using this gene for selecting weightlifters as well as making similar studies on the same gene to identify its correlation with body systems' functions.